ANALISIS PENGARUH STRESS KERJA TERHADAP KINERJA PEGAWAI BAGIAN PELAYANAN PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL DI KOTA PANGKALPINANG (Program Studi Ilmu Kesehatan STIKESÂ Abdi Nusa Pangkalpinang, 2021)
Stress is any stimulation or action from the human body, either from outside or from within the body itself which can cause various adverse effects ranging from decreased health to suffering from a disease. In relation to work, all the effects of stress will lead to reduced performance, efficiency and work productivity.This research was conducted with a descriptive-exploratory qualitative approach. The informants of this study included six front office employees and one front office head. Data collection by in-depth interview methods with the tools used, namely cellphones, stationery and interview guidelines.In this study there is no effect of job stress on employee performance, but with additional tasks from superiors, employees who receive additional assignments from supe riors must complete more quickly. With a comfortable work environment, helping each other, always building, disciplined, firm. However, for the layout of the workspace it is necessary to install a divider to avoid confusion between one counter and another. At the beginning of work, employees often feel afraid and do not understand their job.Addition of dividers or partitions for each section to anticipate that employees who provide information to the community who come to take care of files or documents are not disturbed and are clearer. Training is needed to improve skills / abilities so that their work is easy to understand.